Meiotic studies in ten species of Hybanthus Jacq. (Violaceae) from South America - Seo, M.N. (2009)
Chromosome numbers and meiotic behaviour of 10 native species of Hybanthus in South America were analyzed. 3 different chromosome numbers were found: 2n=16 for Hybanthus atropurpureus (A. St.-Hil.) Taub., H. bigibbosus (A. St.-Hil.) Hassl. and H. paraguariensis (Chodat) Schulze-Menz, 2n=32 for H. bicolor (A. St.-Hil.) Baill., H. calceolaria (L.) Oken, H. communis (A. St.-Hil.) Taub., H. hasslerianus (Chodat) Hassl., H. leucopogon Sparre and H. nanus (A. St.-Hil.) Paula-Souza, and 2n=48 for H. longistylus Schulze-Menz. This is one of the first reports for 8 analyzed species. Nowadays, the basic chromosome numbers in the South American Hybanthus species are under discussion. The presence of 1 tetravalent in H. atropurpureus, H. bigibbosus and H. paraguariensis (2n=16) would suggest the duplication of chromosome sets, and therefore would indicate that the basic chromosome number is x=4, at least, for this group of South American Hybanthus species. The studied species would be tetraploids (2n=4x=16), octoploids (2n=8x=32) and dodecaploids in H. longistylus (2n=12r=48). In light of these findings, such polyploidy would likely have played an important role during the speciation of this heterogenerous generic assembly. © 2009 The Japan Mendel Society.